2000
DOI: 10.1128/aem.66.5.1928-1932.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides Protect Coho Salmon from Vibrio anguillarum Infections

Abstract: Fish losses from infectious diseases are a significant problem in aquaculture worldwide. Therefore, we investigated the ability of cationic antimicrobial peptides to protect against infection caused by the fish pathogen Vibrio anguillarum. To identify effective peptides for fish, the MICs of certain antimicrobial peptides against fish pathogens were determined in vitro. Two of the most effective antimicrobial peptides, CEME, a cecropin-melittin hybrid peptide, and pleurocidin amide, a C-terminally amidated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…The activities of the best peptides against the test strains were comparable to or better than those of gramicidin S and polymyxin B (13).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The activities of the best peptides against the test strains were comparable to or better than those of gramicidin S and polymyxin B (13).…”
Section: Resultsmentioning
confidence: 77%
“…Pleurocidin was isolated from the winter flounder Pleuronectes americanus (Walbaum) in 1997 (9), and its activity has been under investigation by several research groups (13,20,21,23,28). Also, pleurocidin genes have been cloned, and their genetic organization has been described (8, 10; S. E. Douglas, A. Patrzykat, J. Pytyck, and J. W. Gallant, submitted for publication).…”
mentioning
confidence: 99%
“…Amidation of the C-terminal carboxyl increases antimicrobial activity It has been shown that amidation of the C-terminal carboxyl group is able to improve the antimicrobial activity of AMPs (Falla et al, 1996;Oren and Shai, 1996;Jia et al, 2000;Konno et al, 2007). When the structures of the AMP dermaseptin S3 and its amidated analog were compared, Shalev et al found that the amidated dermaseptin has an induced and/or stabilized α-helical conformation, and thus, is more rigid and extended than the nonamidated analog (Shalev et al, 2002).…”
Section: Part IImentioning
confidence: 99%
“…Even though these surfaces are continually exposed to a wide range of potential pathogens, healthy fish are capable of effectively limiting infection. Accumulative evidence is showing that antimicrobial peptides and small proteins may play a major role in protecting fish from such infections (Jia et al 2000). Several types of AMPs have been isolated from fish (see Noga & Silphaduang [2003] for a review).…”
Section: Introductionmentioning
confidence: 99%